(untitled) (Huellas, 2024)
This article aims at analyzing the most important elements of the power relations of irrigation water systems in San Juan and describes the sociopolitical changes that transformed the San Juan water landscape. In this paper, three results are obtained which are worth highlighting. The first one is that the current landscape can be characterized as conservative, rigid, patriarchal, individual and exclusive. The second implies that the possibility of having greater access to water is probably marked by the incorporation of technology and innovation in crops and the modification of some water institutions, which finds limits in the cultural resistance and income of many irrigators. The third one implies that a new hydrosocial cycle is probably developing in the province of San Juan as a consequence of the transformations and the new conformation of forces relationship.